The Dynamic Terrorist Threat An Assessment of Group Motivations and Capabilities in a Changing World - Cragin, Kim (RAND Corporation, 2004)
As the war on terrorism wages on, our nation's policymakers will continue to face the challenge of assessing threats that various terrorist groups pose to the U.S. homeland and our interests abroad. As part of the RAND Corporation's yearlong "Thinking Strategically About Combating Terrorism" project, the authors of this report develop a way to assess and analyze the danger posed by various terrorist organizations around the world. The very nature of terrorism creates a difficulty in predicting new and emerging threats; however, by establishing these types of parameters, the report creates a fresh foundation of threat analysis on which future counterterrorism strategy may build.